2022
DOI: 10.5194/essd-14-2279-2022
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution bathymetry models for the Lena Delta and Kolyma Gulf coastal zones

Abstract: Abstract. Arctic river deltas and deltaic near-shore zones represent important land–ocean transition zones influencing sediment dynamics and nutrient fluxes from permafrost-affected terrestrial ecosystems into the coastal Arctic Ocean. To accurately model fluvial carbon and freshwater export from rapidly changing river catchments as well as assess impacts of future change on the Arctic shelf and coastal ecosystems, we need to understand the sea floor characteristics and topographic variety of the coastal zones… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 51 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…In the case of the ONNS algorithm, neural networks and a blending of their results are chosen through an optical water type classification. Reflectances from the atmospheric correction Case 2 Regional CoastColour (C2RCC, Brockmann et al, 2016) are better exploitable than reflectances from Polymer using the water type classification scheme of ONNS and Juhls et al (2022) showed that a CDOM (440) SAT from ONNS performed worked better with C2RCC spectra, rather than Polymer spectra. A new atmospheric correction is currently under development specially designed for ONNS (Hieronymi et al, 2023).…”
Section: Advances and Challenges Of Optical Remote Sensing To Monitor...mentioning
confidence: 99%
“…In the case of the ONNS algorithm, neural networks and a blending of their results are chosen through an optical water type classification. Reflectances from the atmospheric correction Case 2 Regional CoastColour (C2RCC, Brockmann et al, 2016) are better exploitable than reflectances from Polymer using the water type classification scheme of ONNS and Juhls et al (2022) showed that a CDOM (440) SAT from ONNS performed worked better with C2RCC spectra, rather than Polymer spectra. A new atmospheric correction is currently under development specially designed for ONNS (Hieronymi et al, 2023).…”
Section: Advances and Challenges Of Optical Remote Sensing To Monitor...mentioning
confidence: 99%